RESEARCH ON THE IMPORTANCE OF PROFESSIONAL TRAINING AND SPECIALIST ADVICE FOR FARMERS - A STUDY CASE REGARDING PLANT PROTECTION IN TOMATO GROWING IN GREENHOUSES - Steluța LIPIANU; Cristinel Relu ZALĂ; Costică CIONTU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Professional training and consulting systems in the field of plant protection, and not only, are of particular importance for our country in the context of agricultural policies developed at the level of the European Union. The particularities specific to the implementation of community policies in Romania must be reflected in the level of specialization of agricultural specialists regarding their skills. Agricultural consultancy services represent a vital element in the field of informational and technological transfer in agriculture, providing farmers with information that can contribute to improving their standard of living and that of the rural population. From the research carried out, it appears that Romanian farmers need specialized consultancy in three directions: 1) preparation for accessing European Rural Development Program funds; 2) streamlining plant and animal production; 3) facilitating access to consultants on legal issues, cadastre, feasibility studies, marketing, management, etc. The paper also presents results regarding plant protection products used by farmers in Ilfov county in 2020. The purpose of the paper is assess the farmers knowledge where they could find valuable information to their problems regarding plant protection as reflection of their training level and of the efficiency of the consultancy system in Romania.The working method consisted of a sociological survey and an opinion poll. For technical advice, 28.0% of the surveyed farmers would turn to the Agricultural Directorate. For the use of plant protection products, 51.0% of farmers turned to their delivery company. An important shoulder of farmers, 71.0%, are not aware of the National Action Plan regarding the reduction of risks associated with the use of plant protection products. Most of the farmers, 45.0%, would turn to a private consultant to receive support in accessing European Rural Development Program funds.